2020
DOI: 10.1038/s41586-020-2688-8
|View full text |Cite|
|
Sign up to set email alerts
|

Population genomics of the Viking world

Abstract: The Viking maritime expansion from Scandinavia (Denmark, Norway, and Sweden) marks one of the swiftest and most far-flung cultural transformations in global history. During this time (c. 750 to 1050 CE), Viking sailors reached Greenland, North America, and large parts of western Eurasia, and left a legacy that persists today. To understand the genetic structure and influence of the Viking expansion, we sequenced the genomes of 442 ancient humans from across Europe and Greenland ranging from the Bronze Age (c. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 98 publications
(66 reference statements)
10
140
1
12
Order By: Relevance
“…Through modelling, we were able to show that even when taking into account the possibility of human DNA contamination, it seems likely that the individual had male chromosomal aneuploidy XXY (Klinefelter syndrome). This is not unprecedented, as archaeological cases of Klinefelter syndrome (XXY) have been reported earlier: there is a case from Viking Age Iceland (Ebenesersdóttir et al, 2018), one in early Neolithic Germany (Rivollat et al, 2020), and possibly one from the Orkney Islands in the Viking Age (Margaryan et al, 2020), but the find contexts of these individuals have not been reported as atypical. Therefore, to our knowledge, Suontaka would be the first case of chromosomal aneuploidy from a context which has been puzzling archaeologists as an atypical combination of mixed-gender attributes.…”
Section: Discussionmentioning
confidence: 85%
“…Through modelling, we were able to show that even when taking into account the possibility of human DNA contamination, it seems likely that the individual had male chromosomal aneuploidy XXY (Klinefelter syndrome). This is not unprecedented, as archaeological cases of Klinefelter syndrome (XXY) have been reported earlier: there is a case from Viking Age Iceland (Ebenesersdóttir et al, 2018), one in early Neolithic Germany (Rivollat et al, 2020), and possibly one from the Orkney Islands in the Viking Age (Margaryan et al, 2020), but the find contexts of these individuals have not been reported as atypical. Therefore, to our knowledge, Suontaka would be the first case of chromosomal aneuploidy from a context which has been puzzling archaeologists as an atypical combination of mixed-gender attributes.…”
Section: Discussionmentioning
confidence: 85%
“…However, to demonstrate the application of our pipeline to ultra low coverages, we also included some individuals from these publications that were not included in their original kinship analysis because of coverages below the defined thresholds. For the Church burial of the Faroe Islands in Margaryan et al 16 we included individuals VK239 and VK248 in the analysis, with coverages below the publication’s threshold of 0.1x (0.027× and 0.076×, respectively), and identified a new 2nd-degree relationship for VK239–VK237 (Table 1 ). In the case of Saag et al 17 , for Toomani (Muuksi) we included individuals X05, X06, and X07, who have coverages below their threshold of 0.03× (0.0290×, 0.0048×, and 0.0059×, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…However, imputation itself introduces a new source of bias, particularly if the reference panel is not representative of the ancestries found in the low-coverage samples. Nevertheless, the level of imputation bias can be empirically estimated by downsampling high-coverage aDNA libraries and testing imputed genotypes against direct observations (e.g., Margaryan et al, 2020 ). Where a suitable reference panel exists, recently developed methods for imputation from low-coverage sequencing data ( Davies et al, 2021 ; Rubinacci et al, 2021 ) show great promise for ancient DNA studies (e.g., Clemente et al, 2021 ).…”
Section: Limitations and Caveats Specific To Ancient Dnamentioning
confidence: 99%